A systematic review of service-user reasons for adherence and nonadherence to neuroleptic medication in psychosis. (February 2017) - Wade, Miriam; Tai, Sara; Awenat, Yvonne; Haddock, Gillian
Abstract: People diagnosed with psychosis, such as those with schizophrenia-related disorders, are routinely prescribed neuroleptic medication as a primary treatment. Despite reported benefits of neuroleptic treatment for symptom remission and relapse prevention, discontinuation rates are high. Research examining factors associated with neuroleptic non-adherence report inconsistent findings. Reasons for adherence to neuroleptic medication are under-researched. The current review aimed to synthesise evidence exploring service-user self-reported reasons for adherence and non-adherence to neuroleptic medication. A systematic literature search of databases and reference list searching identified 21 studies investigating service-user accounts of reasons for adherence and/or non-adherence to neuroleptic medication. Qualitative, quantitative and mixed-method studies were included in the review. Several themes of reasons were identified. Reasons for both adherence and non-adherence were largely similar; medication efficacy, compatibility with personal medication or religious beliefs, side-effects and the influence of relationships with other people. Experiences of stigma and economic difficulties were generally identified as reasons for non-adherence only while experiences of fear and coercion were identified as reasons for adherence only. The review identified crucial factors which may aid service providers in bettering treatment for people with psychosis and will provide evidence which could contribute to future prescribing guidelines. Highlights: Service-users with psychosis often discontinue neuroleptic medication. Service-user reasons for adherence and non-adherence are reviewed. Several themes of reasons are identified across studies of differing methodologies.